Legal protection of particular time contract workers in job creation - Sudin, Amatus; Isnaeni, Moch; Suhartono, Slamet (Technium Social Sciences Journal, 2022)
This type of research is a normative juridical research by using laws and regulations. The Job Creation Law regulates several new provisions for certain time contract workers when compared to the previous arrangements in the Manpower Act. These new provisions are a form of legal protection for certain time contract workers. These provisions can be summarized as follows: a longer period of time for a work agreement for a certain time, a work agreement for a certain time in written form. This is to provide legal certainty to workers regarding the existence of a work agreement relationship between workers and employers.